2021
DOI: 10.31234/osf.io/rkfg7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attentional control in middle childhood is highly dynamic - Strong initial distraction is followed by advanced attention control

Abstract: The ability to shield against distraction while focusing on a task requires the operation of executive functions and is essential for successful learning. We investigated the short-term dynamics of distraction control in a data set of 269 children aged 4–10 years and 51 adults pooled from three studies using multilevel models. Participants performed a visual categorization task while a task-irrelevant sequence of sounds was presented which consisted of frequently repeated standard sounds and rarely intersperse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Volkmer et al. (2022) examined the short‐term dynamics of distraction control in children and adults using multilevel models. They found that on average, participants responded slower in the categorization task after novel sounds and that this distraction effect was more pronounced in children.…”
mentioning
confidence: 99%
“…Volkmer et al. (2022) examined the short‐term dynamics of distraction control in children and adults using multilevel models. They found that on average, participants responded slower in the categorization task after novel sounds and that this distraction effect was more pronounced in children.…”
mentioning
confidence: 99%